AN ANALYSIS OF UNDERGRADUATE EFL STUDENTS’ LEARNING EXPERIENCES IN USING GOOGLE TRANSLAT ION CLASS - Dede Krisdayanti (Universitas Galuh, 2022)
The present study is aimed to determine the learning experience of undergraduate students in using Google Translate in the translation class. This study uses a qualitative research design under the characteristics of a case study. Data were obtained through interviews conducted by researchers with 4 participants at level 3 of the English Education Study Program who takes elective courses in translation classes at one of the private universities in West Java. The findings reveal that Google Translate is an online translation tool that really helps students in learning. However, the results of the Google Translate translation should not be taken for granted because they need to be improved again. Lecturers do not recommend the use of Google Translate in translation classes because of the negative impact that can make students lazy to develop their abilities and the translation results are considered inaccurate. Based on these findings, it is recommended for teachers to be innovative in using Google Translate as a learning aid and students should limit the use of Google Translate and not feel dependent.